A sustentabilidade na formação de engenheiras e engenheiros químicos da UFSCar: percepções, demandas e perspectivas - Marcato, Raissa Guidolin (Universidade Federal de São Carlos, 2022)
According to the 3º Article, V and VI from the 2nd resolution which constitutes the new National Curriculum Guidelines of 2019 to every major in the engineering, it is expected that the graduates of the engineering major have a profile and skills that consider global, political, economic, social, environmental, cultural and occupational health and safety aspects, and they act with impartiality and commitment to social responsibility and sustainable development. Based on the new National Curriculum Guidelines, the main goal of this project is to analyze the global scenery and present demands, perceptions and perspectives for the inclusion and deepening of the sustainability theme in the pedagogical project of Chemical Engineering at UFSCar (Universidade Federal de São Carlos). From the understanding of the current scenery of the job market and using as reference the majors in Chemical Engineering in Brazil and overseas, changes were proposed in the goals of the current disciplines aiming the best preparation and education of students in aspects os sustainability. In this regard, the curriculum of Chemical Engineering in other universities went through studies and research. Along the market, there was a survey to understand what the expectations of professionals in sustainability issues are. The survey contained information from current and former students of Chemical Engineering to understand their perspectives and demands related to the topic. The collected data were analyzed, and based on the result a proposal was designed involving changes in the goals and menus of the subjects of the college program. From this proposal, it is intended to adapt and modernize the graduation of chemical engineers with a robust vison of sustainability within the expertise and tools of Chemical Engineering. It is expected that the work will have a great contribution in the curricular reformulation of the Pedagogical Project of the Course and, consequently, in the insertion of these professionals in the job market due to the extreme relevance of the topic in the current world.
Sustentability in the formation of chemical engineers at UFSCar: perceptions, demands and perspectives
Keywords: Sustentabilidade; Diretrizes curriculares nacionais; Reformulação projeto pedagógico; Estratégia de ensino e aprendizagem; Sustentability; National curriculum guidelines; Pedagogical project reformulation; Teaching learning strategy; ENGENHARIAS::ENGENHARIA QUIMICA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::TEORIAS DA INSTRUCAO